Poetries by Giuseppe Parini: textual issues (Prassi Ecdotiche della Modernità Letteraria, 2018)
In the process of publishing the Odi (1791), Giuseppe Parini assembled the collection of his scattered poems, composed over a long period of time, with the help of the pupil Agostino Gambarelli (ms. Ambrosiano III.4); the anthology should have been a sort of pendant of the juvenile Poesie di Ripano Eupilino (1752). After Gambarelli’s death (1792), Parini entered a broad process of revision of the III.4, with corrections that changed the original physiognomy; but the editorial project not come to an end. The paper describes the textual structure of a segment of III.4, which includes fifteen poems of various meters (then reduced to twelve), the most important of which (from the philological point of view) is the final text I Ciarlatani (1762-1763).
Keywords: Giuseppe Parini; Agostino Gambarelli; poetry; collection; variants; author's will